Intelligent distributed video surveillance systems - Velastin, Sergio A.; Remagnino, Paolo 1963- (London, United Kingdom Institution of Engineering and Technology, 2006)
The book reviews developments in the following fields: distributed video surveillance system; system design; distributed database for effective management and evaluation of CCTV system; distributed domestic surveillance system; general-purpose system for distributed surveillance and communication; object tracking; uncalibrated arbitrary topology camera networks; distributed multisensor surveillance system for public transport applications; football player tracking; and hierarchical multisensor framework for event detection in wide environments.
Electronic reproduction.
Keywords: Computer vision; Electronic surveillance; Optical pattern recognition; Imaging systems; Signal processing; Human behavior; Electronic books